ORGANIZATIONAL TRUST OF FACULTY MEMBERS AND ITS RELATIONSHIP TO TEAM-BUILDING CAPACITY AND TEACHING EFFECTIVENESS - Addun, Beverly M. (International Journal of Psychosocial Rehabilitation, 2020)
This study was an investigation of the organizational trust of faculty members of a university in the Philippines and its relationship to their team building capacity and teaching effectiveness. It uses a quantitative design utilizing the descriptive-correlational method. The respondents of this study were dominantly female, in their middle adulthood and master’s degree holders. Their average length of service in the university is almost two decades. The study concludes that the university under study has a promising instructional staff imbued with high level of organizational trust, team building capacity and teaching effectiveness. Altogether, they exhibit positive attitude such as high morale, effective task performance and a clear relevance to the university as they work interdependently, are committed to common goals, and produce very good instructional performance. The study has proven that a major factor that influences the team building capacity of the faculty members is their organizational trust. This shows that there is indeed a positive or direct relationship between organizational trust and team building capacity. However, the study disproves some studies claiming the direct relationship between organizational trust and teaching effectiveness. Interestingly, the only demographic variable that influences organizational trust of teachers is their length of service. But with respect to teaching effectiveness, the study concludes that sex, age, and educational attainment of teachers are factors that influence teachers’ level of teaching effectiveness. Essentially, male, young and those with lower educational attainment are teachers who have higher teaching effectiveness. Finally, the study has demonstrated that team building capacity is not influenced or has no positive relations with the teachers’ sex, age, educational attainment, academic rank and length of service.